Konsep Nilai-Nilai Pendidikan Karakter (Telaah Pedoman Kemendiknas 2010) - Rayhanur Royyan; Hidayat, Nur (Wacana Akademika: Majalah Ilmiah Kependidikan, 2024)
Character education is something that is important for every student and teacher to know and implement because it will have a big impact on the future progress of the nation. This research aims to determine the concept of character education values contained in the 2010 Ministry of National Education Guidelines and the implementation of these values in each educational unit. The research method used is library research with a qualitative research type. In collecting data, this research carried out documentation and content analysis of relevant data sources. Meanwhile, data analysis in this research uses technical analysis proposed by Milss and Huberman. The results of this research state that the character education values contained in the Ministry of National Education Guidelines consist of 18 values. From these 18 values, several indicators have been determined so that they can be implemented in each educational unit.